THE ROLE OF ASSET DEPRECIATION IN THE COMPANY'S FINANCIAL INDICATORS AND ITS IMPROVEMENT - Sayfullayev Mexroj Sayfullayevich (Research Parks Publishers, 2023)
In this article, the role of asset impairment losses in the company's financial indicators and proposals for its improvement are developed.